The Impact of Coronary Artery Endarterectomy on Outcomes During Coronary Artery Bypass Grafting - LaPar, Damien J. (2011)
BACKGROUND: The impact of coronary artery endarterectomy during coronary artery bypass grafting (CABG) has been debated. We examined the early and late outcomes of CABG with endarterectomy (CE) compared to CABG alone. METHODS: Patients undergoing isolated CABG operations from 2003 to 2008 were retrospectively reviewed. We identified 99 patients who underwent CE and 3:1 propensity matched them to 297 CABG-alone patients based upon clinical factors: Society of Thoracic Surgeons (STS) predicted risk of mortality, age, gender, year of surgery, and ejection fraction. Patient risk factors as well as short-and long-term outcomes were compared by univariate and Kaplan-Meier analysis. RESULTS: Preoperative risk factors were similar between patients undergoing CE or CABG alone. Cross-clamp times (95.6 vs. 71.8 minutes, p = 0.0001) and perfusion times (121.8 vs. 92.7 minutes, p = 0.0001) were longer in patients undergoing CE. Operative mortality (4.0% vs. 1.3%, p = 0.112) and postoperative complications were not significantly different between groups. Patients undergoing coronary endarterectomy incurred longer ICU (75.06 vs. 48.64 hours, p = 0.001) and hospital stays (9.01 vs. 7.7 days, p = 0.034). Long-term mortality (mean follow-up = 27.7 ± 17.7 months) was equivalent despite revascularization technique (p = 0.13); however, patients undergoing CE encountered worse overall freedom from myocardial infarction (MI) (p = 0.03). CONCLUSION: Patients undergoing CABG with coronary CE required longer ventilatory support and ICU stay yet have comparable operative mortality, major complication rates, and long-term survival to isolated CABG. Coronary endarterectomy should be considered an acceptable adjunct to CABG for patients with extensive coronary artery disease to achieve complete revascularization.